Is it possible to enhance face recognition skills? The effect of transcranial direct current stimulation (tDCS) and image-variability training - Kho, Siew Kei (2024)
Face recognition ability is important for social interaction that occurs in our everyday lives. Given the importance of faces in social interactions, losing the ability to recognize faces may produce devastating consequences for an individual’s social life. Improvement of face recognition ability is important not only for individuals with facial recognition deficits, but also for national security. Thus, the main aim of this thesis is to examine the effect of transcranial direct current stimulation (tDCS) and cognitive training on own- and other-race face recognition.